2012
DOI: 10.1016/j.jadohealth.2012.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Health Consequences of Screen-Time Change During Adolescence—1993 Pelotas (Brazil) Birth Cohort Study

Abstract: PurposeTo investigate screen-time change from early to mid adolescence, its predictors, and its influence on body fat, blood pressure, and leisure-time physical activity.MethodsWe used data from a longitudinal prospective study, conducted among participants of the 1993 Pelotas (Brazil) Birth Cohort Study. At baseline, adolescents were, on average, 11 years old. They were later visited at age 15 years. Screen time was self-reported, accounting for the time spent watching television, playing video games, and usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 37 publications
7
36
0
3
Order By: Relevance
“…There was a high prevalence of adolescents who did screen-related activities for more than two hours daily, corroborating other findings 3,7,13 . When considering the sedentary activities separately, it was observed that the prevalence of each one differs according to gender, age and SES.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…There was a high prevalence of adolescents who did screen-related activities for more than two hours daily, corroborating other findings 3,7,13 . When considering the sedentary activities separately, it was observed that the prevalence of each one differs according to gender, age and SES.…”
Section: Discussionsupporting
confidence: 89%
“…There is also indication that this behavior increases throughout adolescence. For example, in a longitudinal study with 4,218 adolescents, an average increase of 60 minutes/ day per year in the screen time in adolescents aged 11 and 15 years was observed; and this increase was associated with body adiposity 7 . In addition, this behavior is more likely to continue into adulthood 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional studies of watching television and computer use in children and adolescents indicate that children who spend more time watching television are more likely to be overweight or obese and also to be less physically active (19,30,48,49). In general, screen time is important contribution to the overall time spent indulging in sedentary behaviour.…”
Section: Public Health Implicationsmentioning
confidence: 99%
“…Some studies reported a consistent amount of the total time spent sitting in front of a television or a computer, and they reveal that the time spent watching television was replaced by time spent using a computer (28,29). Other studies found an increase in the time spent sitting in front of a television or computer (30)(31)(32). Further analyses that use the same methodology in different countries are needed to facilitate sound comparisons between countries.…”
Section: Introductionmentioning
confidence: 99%
“…Dumith et al provide more information on the predictors and health consequences of screen time during adolescence. Screen time increased from 11 to 15 years of age, particularly among boys and high-income adolescents [9]. This increase in screen time predicted adiposity in this cohort.…”
mentioning
confidence: 72%